Human bodies in virtual worlds: a systematic review of implicit sense of agency and ownership measured in immersive virtual reality environments - Girondini, Matteo; Mariano, Marika; Stanco, Giulia; Gallace, Alberto; Zapparoli, Laura (Frontiers in Human Neuroscience, 2025)
IntroductionVirtual reality (VR) offers novel tools for investigating the sense of agency (SoA) and sense of body ownership (SoO), key components of bodily self-consciousness, by enabling experimental manipulations beyond traditional paradigms. This review systematically examines how these manipulations affect SoA and SoO, focusing on their implicit indexes (e.g., intentional binding, proprioceptive drift) and their alignment with explicit measures.MethodsWe clustered the manipulations based on their targeted mechanisms and evaluated their effects on SoA and SoO. Agency manipulations altered the relationship between real and virtual actions, in terms of visuomotor congruence (e.g., temporal or spatial misalignment between actions and outcomes) and movement control (e.g., replacing user actions with pre-recorded movements). Ownership manipulations focused on altering characteristics of the virtual body or limb, including physical congruence (e.g., realistic vs. object-like representations), spatial congruence (e.g., alignment of virtual and real body positions), and stimulation congruence (e.g., synchronous vs. asynchronous visuotactile feedback).ResultsAgency manipulations had a strong effect on implicit SoA, while only visuomotor congruence produced a mild effect on implicit SoO. Ownership manipulations influenced implicit SoO to different extents: spatial congruence and stimulation congruence exerted moderate effects, while physical congruence showed mild effects. None of these manipulations affected implicit SoA. The alignment between implicit and explicit measures was heterogeneous, indicating that these indexes may capture distinct underlying processes. We observed that agency manipulations showed limited agreement across both SoA and SoO indexes, while ownership manipulations exhibited high agreement on SoA indexes and moderate agreement on SoO indexes.DiscussionThese findings demonstrate that SoA and SoO can be functionally dissociated through targeted VR manipulations—for example, changes in body appearance did not affect implicit agency. However, SoA and SoO also show context-dependent interactions, as seen with visuomotor congruence manipulations influencing implicit SoO. This highlights their partial independence and dynamic interplay within embodied self-representation. Overall, virtual reality offers a valuable tool for exploring SoA and SoO through paradigms that overcome the limits of the traditional laboratory context. Crucially, our review identifies which types of manipulations tend to selectively influence one experience versus those that affect both, providing a framework for designing more targeted and theory-driven future studies.